The inclusion membrane protein IncS is critical for initiation of the Chlamydia intracellular developmental cycle. - María Eugenia Cortina; R Clayton Bishop; Brittany A DeVasure; Isabelle Coppens; Isabelle Derré (PLoS Pathogens, 2022)
All Chlamydia species are obligate intracellular bacteria that undergo a unique biphasic developmental cycle strictly in the lumen of a membrane bound compartment, the inclusion. Chlamydia specific Type III secreted effectors, known as inclusion membrane proteins (Inc), are embedded into the inclusion membrane. Progression through the developmental cycle, in particular early events of conversion from infectious (EB) to replicative (RB) bacteria, is important for intracellular replication, but poorly understood. Here, we identified the inclusion membrane protein IncS as a critical factor for Chlamydia development. We show that a C. trachomatis conditional mutant is impaired in transition from EB to RB in human cells, and C. muridarum mutant bacteria fail to develop in a mouse model of Chlamydia infection. Thus, IncS represents a promising target for therapeutic intervention of the leading cause of sexually transmitted infections of bacterial origin.